Genotypic variation for grain yield and grain nitrogen concentration among sorghum hybrids under different levels of nitrogen fertiliser and water supply - Kamoshita, A.; Cooper, M.; Muchow, R.C.; Fukai, S. (Commonwealth Scientific and Industrial Research Organisation, 1998)
Sorghum [Sorghum bicolor (L.) Moench] is often grown under nitrogen- or water-limited conditions, but there is little information on genotypic variation for grain yield and grain nitrogen (N) concentration under these conditions. This study examined the expression of specific adaptation of hybrids to these stress conditions and, secondly, the effect of N fertiliser application on yield and grain N concentration of the hybrids. Two experiments, one irrigated and the other under rainfed conditions, were conducted in 2 seasons to examine 14 hybrids grown under 3 levels of fertiliser N supply (0, 60, and 240 kg/ha). Genotypic variation for yield and grain N concentration was generally larger than the in˚uence of genotype environment (predominantly N and water) interactions. Genotypic variation for phenology was important in determining variation for yield and grain N concentration in high-input and rainfed conditions when N was not the limiting factor, but not under N-limiting conditions. Under high-input conditions (240 kg/ha of N fertiliser and irrigated), maturity date accounted for about 50% of the genotypic variation for grain yield (798-1049 g/m2), with later maturing hybrids having a higher yield. Maturity date had little effect on plant N content at maturity or N harvest index, and hence grain N concentration (1·67-2·01%) was negatively correlated with grain yield. Under N-limiting conditions, N fertiliser application had large effects on yield and/or grain N concentration in both well-watered and pre-anthesis water stress conditions. In the irrigated experiment, when N was limiting (0 and 60 kg/ha of N fertiliser), genotypic variation for grain yield (225-729 g/m2) was not related to that for maturity date. It was, however, related to the variation in N uptake and dry matter growth by anthesis in the non-fertilised treatment. There was significant genotypic variation for grain N concentration (0·94-1·26%), which was not explained by variation for grain yield. Under rainfed conditions, where severe pre-anthesis water stress occurred, phenology was important in determining about 40% of the genotypic variation for yield (69-286 g/m2). The late-flowering hybrids escaped the major impact of the pre-anthesis water stress, had reduced damage to panicle development, and had higher N utilisation, consequently producing higher grain yield. Grain N concentration (1·09-2·85%) was again negatively related with grain yield. Genetic improvement of N uptake is identified as a possible breeding strategy for raising productivity and quality of grain sorghum under N-limiting conditions.